Perspectivas del anciano latinoamericano a las puertas de un nuevo siglo - Luna Torres, Leonor (Avances en Enfermería, 1997)
The world will beth scen ery of an unknocun success when this century finishes. The growing I old of the actual population is a reality that for latinamerica starts its evidence, this situation is starting to demand programs population, that give attention to the ancient population, the same that today registrat a life expectation of seventy (70) years and more for contries like Cuba, Colombia and Costa Rica. Although nation like Haiti and Dominican Republic can't even reach an average of sixty (60) years. The article describe the antecedents of the creation of policies and programs, calls the attention the important necesity of creatings new culture of the ancianity in the participation of the men, the family, the state and society in an explicit way to convoke the nursing professionals to participate in this iniciative.